A PREDICTION SYSTEM DESIGN FOR THE AMOUNT OF CORN PRODUCTION USING TSUKAMOTO FUZZY INFERENCE SYSTEM - Fitria - (Proceeding International Conference on Information Technology and Business, 2015)
Fuzzy inference system is a computing framework basedon fuzzy set theory, fuzzy rules in the form of IF-THEN,and fuzzy reasoning. Fuzzy inference system receivesinput crisp. This input is then sent to a knowledge base thatcontains fuzzy rules in the form of IF-THEN. Fire strengthwill be sought at every rule. If the number of rules is morethan one, it will be the aggregation of all the rules.Furthermore, the aggregation results will be defuzzy to getcrisp value as output system (Kurniawan, 2004).The method used in building this system is the method ofTsukamoto fuzzy inference system. Tsukamoto method isan extension of the monotonous reasoning. In Tsukamotomethod, each consequent upon the rules that forms If -Then shall be represented by a fuzzy set membershipfunctions are monotone.The results of this study are to predict number ofinformation systems on corn production in the SPSS SouthLampung District Court and to get the desired resultsKEY WORDS: corn production information system, theprediction system